A brief school-based intervention on Gypsy culture: A longitudinal cluster randomized trial. Issue 6 (29th November 2020) - Rosário, Pedro; Pereira, Beatriz; Magalhães, Paula; Moreira, Tânia; Mesquita, Sandra; Fuentes, Sonia; Núñez, José Carlos; Vallejo, Guillermo
Abstract: Gypsy children low school engagement, high rates of school dropout, and pervasive school failure are relevant societal challenges that may be explained by Gypsy people cultural mores, but also by the discriminatory behaviors of school peers. The latter may be a consequence of insufficient accurate knowledge of Gypsy culture. The present study developed a brief school-based intervention targeting the whole class with a focus on raising awareness of Gypsy culture, the educational aspirations of Gypsy students, and their experiences with discrimination. To assess the effectiveness of the intervention, 88 classes encompassing 1505 fourth and fifth grades students enrolled in Portuguese schools were randomly assigned to one of three conditions: Control Group, Focused on the Domain Group (Gypsy culture), and Non-Focused on the Domain Group (general non-dominant cultural groups such as immigrants). These groups were assessed in three waves: pretest, post-test, and follow-up. Data from this longitudinal cluster randomized trial showed the efficacy of this brief intervention in decreasing reported social distance and increasing positive attitudes toward Gypsy people. Importantly, results from the Focused on the Domain Group intervention were more positive than the Non-Focused on the Domain Group. Implications for educational practice are discussed.